(untitled) (International Journal of Current Research in Physiology and Pharmacology, 2021)
We assessed the ameliorative effect of Virgin Coconut Oil following atrazine-induced metabolic derangement in rats. Adult male wistar rats weighing 180-200g were used; randomly separated into two major groups. Thirty-five rats in the test group were randomly divided into five sub-groups of 7 rats per sub-group and treated thus: Sub-group (SG) 1, 2 and 3 received 10ml/kg of distilled water, 10ml/kg VCO, 123mg/kg of Atrazine respectively, SG4 was diabetic control; SG 5 was the diabetic group treated with 10ml/kg of VCO for 2 weeks, after which the animals were sacrificed and blood collected for analysis. 35 rats for the recovery group were also divided into 5 sub-groups of 7 rats per sub-group and were treated; SG 1, 2, 3, 4 and 5 received 10ml/kg distilled water, 10ml/kg VCO, 123mg/kg of ATZ respectively. After 2 weeks, the animals were re-treated thus: SG 1,2,3,4 and 5 received 10ml/kg of distilled water, 10ml/kg of VCO, 123mg/kg of ATZ, 10ml/kg VCO and 10ml/kg distilled water respectively. After 2 weeks, the animals were also sacrificed and blood collected for analysis. ATZ reduced serum insulin and a reduced expression of GLUT4. VCO restored GLUT4 levels but did not significantly restore the insulin to the normal levels